CESifo World Economic Survey February 2015 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Tim Oliver Berg (CESifo World Economic Survey, 2015)
World Economic Climate: World Economic Climate remains almost unchanged - Economic Expectations: Economic expectations barely improved - Inflation:Low inflation expectations - Currencies: US dollar expected to rise - Interest Rates: Interest rates look set to remain stable - Special Topic: Bank asset quality reviews, stress tests and their perception in terms of transparency and investor confidence
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies